Pengetahuan Pria Tentang Andropause Di RW 11 Kelurahan Perhentian Marpoyan Kecamatan Marpoyan Damai Pekanbaru - Wiwik Norlita; Isnaniar Isnaniar; Rahmat Hidayat (Sistem Informasi, 2019)
Andropause prevalence can be estimated based on population projections. The number of men who experience andropause in Indonesia has no official data. In the United States the data states that andropause syndrome is experienced by around 15 percent of men aged 40-60, but only about 5 percent get treatment. Some men have even experienced andropause syndrome since the age of 30, but with a relatively small amount of about 5 percent (pangkahila, 2007). Based on the results of the initial survey conducted by researchers on 7-8 August 2018 in the RW of Perhentian Marpoyan Sub-District, Marpoyan Damai Subdistrict, from 10 respondents, there were 4 results (40 percent) who knew about andropause and 6 respondents (60 percent) did not know about andropause aim : identify men's knowledge about andropause in RW 11 of Perhentian Marpoyan Village, Marpoyan Damai District, Pekanbaru. Method : Researcher's design used is quantitative with descriptive design, which is a method of researchers carried out with the main goal to make a description or description of an objective situation (Nototmodjo, 2010). The results : It was found that the majority of families had insufficient knowledge of 55 respondents (76.4%) who had sufficient knowledge of 4 respondents (5.6%) and only 13 respondents (18.1%) had good knowledge. Conclusion : It is expected that the family can add insight into andropause so that it can increase the knowledge of the family head who has sufficient and insufficient knowledge.